![image](https://tex.z-dn.net/?f=%285-x%29%5E2%3D3x%285-x%29+%5C%5C++%5C%5C+25-10x%2Bx%5E2%3D15x-3x%5E2+%5C%5C++%5C%5C+4x%5E2-25x%2B25%3D0+%5C%5C++%5C%5C+D%3Db%5E2-4ac%3D25%5E2-4%2A4%2A25%3D225%3E0+%5C%5C++%5C%5C+x_1%3D+%5Cfrac%7B-b-+%5Csqrt%7BD%7D+%7D%7B2a%7D%3D+%5Cfrac%7B25-+%5Csqrt%7B225%7D+%7D%7B2%2A4%7D%3D1%2C25++%5C%5C++%5C%5C+x_2+%3D%5Cfrac%7B-b%2B+%5Csqrt%7BD%7D+%7D%7B2a%7D%3D+%5Cfrac%7B25%2B%5Csqrt%7B225%7D+%7D%7B2%2A4%7D%3D5)
0 \\ \\ x_1= \frac{-b- \sqrt{D} }{2a}= \frac{25- \sqrt{225} }{2*4}=1,25 \\ \\ x_2 =\frac{-b+ \sqrt{D} }{2a}= \frac{25+\sqrt{225} }{2*4}=5" alt="(5-x)^2=3x(5-x) \\ \\ 25-10x+x^2=15x-3x^2 \\ \\ 4x^2-25x+25=0 \\ \\ D=b^2-4ac=25^2-4*4*25=225>0 \\ \\ x_1= \frac{-b- \sqrt{D} }{2a}= \frac{25- \sqrt{225} }{2*4}=1,25 \\ \\ x_2 =\frac{-b+ \sqrt{D} }{2a}= \frac{25+\sqrt{225} }{2*4}=5" align="absmiddle" class="latex-formula">